2022
DOI: 10.1111/codi.16080
|View full text |Cite
|
Sign up to set email alerts
|

Operative, long‐term and quality of life outcomes after salvage of failed re‐do ileal pouch anal anastomosis

Abstract: Aim Approximately 20%–40% of the patients with re‐do ileal pouch anal anastomosis (IPAA) experience pouch failure. Salvage surgery can be attempted in this patient group with severe aversion to permanent ileostomy. The literature regarding secondary IPAA revision after re‐do IPAA failure is scarce. Methods All patients who underwent a secondary IPAA revision after re‐do IPAA failure between September 2016 and July 2021 in a single centre were included. Short‐ and long‐term outcomes and quality of life in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…8,10,11 Despite the lack of statistical significance, the trend toward higher pouch failure in the cohort with a final diagnosis of CD suggests that a careful preoperative work up is warranted in those patients. However, the overall pouch retention rate was similar to that reported by Esen et al, 9 who in their study had 10 patients who underwent a second redo pouch procedure, 9 and comparable to the retention rate of first redo pouches. 7,8 Affording patients an acceptable quality of life without a permanent ileostomy is the ultimate goal of any pouch salvage procedure.…”
Section: Discussionsupporting
confidence: 87%
“…8,10,11 Despite the lack of statistical significance, the trend toward higher pouch failure in the cohort with a final diagnosis of CD suggests that a careful preoperative work up is warranted in those patients. However, the overall pouch retention rate was similar to that reported by Esen et al, 9 who in their study had 10 patients who underwent a second redo pouch procedure, 9 and comparable to the retention rate of first redo pouches. 7,8 Affording patients an acceptable quality of life without a permanent ileostomy is the ultimate goal of any pouch salvage procedure.…”
Section: Discussionsupporting
confidence: 87%
“…Centralizing the care of patients undergoing primary and revisional ileoanal pouch surgery in few dedicated pouch units, could result in increased volume of activities, making it more appropriate for those units to invest into the service, with resulting bene ts for training and nurturing expertise across different specialties. As a matter of fact, gaining experience in pouch surgery is not easy, as the procedure is performed infrequently across many hospitals, as reported by the UK Pouch registry [1], outlining that the average number of pouches performed in English institutions was just three cases per year and one quarter of the surgeons undertaking this operation had performed only one case over the last ve years.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical complications of the ileoanal pouch affecting function and quality of life may require surgical correction or pouch excision [1]. It is well known that ileoanal pouch surgery is performed infrequently, making it di cult for surgeons and multidisciplinary team members to develop expertise in ileoanal pouch anastomosis (IPAA) surgery [2], and even more in revisional and excisional surgery.…”
Section: Introductionmentioning
confidence: 99%
“…33 Pushing the envelope, this latter group reported a small series of 10 patients that underwent a second redo IPAA, with a follow up of 28 months, pouch retention rate was 78%. 34 In terms of functional outcomes and QOL, patients that underwent revisional surgery seem to fare worse than patients with a primary pouch. A recent meta-analysis of revisional ileoanal pouch surgery compared with primary pouches, with 2,400 patients found that revisional surgery was associated with a greater frequency of day-time bowel movements (4.1 vs. 7.4, p < 0.0001), a greater frequency of night-time bowel movements (2.6 vs. 1.8, p < 0.002), a higher proportion of patients reporting fecal incontinence (62.3% vs. 34.8%, p ¼ 0.0119), a higher proportion of patients reporting urgency/soiling (20.8% vs. 3.8% p ¼ 0.0062), as well as worse QOL evaluated with the Cleveland Global Quality of Life Questionnaire.…”
Section: Outcomes Of Revisional Pouch Surgery Operative Variablesmentioning
confidence: 99%
“…33 Pushing the envelope, this latter group reported a small series of 10 patients that underwent a second redo IPAA, with a follow up of 28 months, pouch retention rate was 78%. 34…”
Section: Outcomes Of Revisional Pouch Surgerymentioning
confidence: 99%